Paroxysmal Nonkinesigenic Dyskinesia with Tremor - Robert Fekete (Case Reports in Neurological Medicine)
Introduction. Paroxysmal nonkinesigenic dyskinesia (PNKD) consists of episodes of chorea, athetosis, or dystonia which are not triggered by movement, with complete remission between episodes. A case of genetically confirmed PNKD with simultaneous tremor has not been previously reported. Case Report. The patient is an 86-year-old right-handed female who presented with episodic stiffness, with onset at age 9. Attacks have a prodrome of difficulty in speaking, followed by abnormal sensation in extremities. Episodes consist of dystonia of trunk associated with upper and lower extremity chorea. There is complete resolution between attacks except for persistent mild head tremor and action tremor of both extremities. Attack frequency and duration as well as tremor amplitude escalated two and a half years ago, in correlation with development of breast carcinoma. Episodes improved after successful cancer treatment, but higher amplitude tremor persisted. There is an autosomal dominant family history of similar episodes but not tremor. Genetic diagnosis was confirmed via A7V mutation of the myofibrillogenesis regulator (MR-1) gene. Conclusion. Exacerbation due to another medical or psychiatric condition should be considered if there is unexpected deterioration in episode frequency or length. PNKD due to MR-1 mutation may exist even in the presence of action tremor.